2015
DOI: 10.1007/s13277-015-3178-8
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses lymphatic vessel density in an in vivo human gastric cancer model

Abstract: This study aimed to assess the effects of curcumin on lymphatic vessel density (LVD) in an in vivo model of gastric cancer using the gastric cancer cell line, SGC-7901. Gastric tumor-bearing nude mice were treated with saline or 40, 80, or 160 mg kg(-1) day(-1) curcumin for 8 weeks. The results indicated that the tumor volumes were significantly lower in mice treated with 80 and 160 mg kg(-1) day(-1) curcumin as compared with that of the control group (both P < 0.001). In addition, both 80 and 160 mg kg(-1) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
2
22
1
1
Order By: Relevance
“…However, the effect of curcumin on human gastric cancer and the underlying mechanisms have not been well documented. Previous studies demonstrated that curcumin attenuates gastric cancer cell proliferation, induces apoptotic cell death and suppresses lymphatic vessel density in vivo or in vitro (27)(28)(29). In the present study, we provided the first evidence that curcumin inhibited cell growth and induced protective autophagy against apoptotic cell death in human gastric cancer.…”
Section: Discussionsupporting
confidence: 63%
“…However, the effect of curcumin on human gastric cancer and the underlying mechanisms have not been well documented. Previous studies demonstrated that curcumin attenuates gastric cancer cell proliferation, induces apoptotic cell death and suppresses lymphatic vessel density in vivo or in vitro (27)(28)(29). In the present study, we provided the first evidence that curcumin inhibited cell growth and induced protective autophagy against apoptotic cell death in human gastric cancer.…”
Section: Discussionsupporting
confidence: 63%
“…Besides, the combination of Kruppel-like factor 4 (KLF4) overexpression and curcumin had significant anti-proliferation, pro-apoptosis and anti-invasion effects on human gastric carcinoma cells, indicating that KLF4 was a potential therapeutic target, and curcumin was a promising therapeutic drug in stomach cancer [62]. In addition, lymphatic vessel density was reduced by curcumin in an in vivo human gastric cancer model, lymphatic vessel endothelial receptor 1 (LYVE-1), prospero homeobox 1 (Prox-1), podoplanin, and vascular endothelial growth factor receptor 3 (VEGFR-3) mRNA expression were down-regulated, which indicated gastric cancer lymph node metastasis might be inhibited by curcumin [63]. Besides, curcumin inhibited cancer cell growth, induced cell cycle arrest at G 2 /M phase, and down-regulated glycolytic enzymes expressions, thus blocking cell growth [64].…”
Section: Turmeric and Curcuminmentioning
confidence: 99%
“…Curcumin in combination with 5-FU was found to synergistically inhibit survivin and STAT3 levels resulting in enhanced cell death of gastric cancer cells and are consequently, suggested as an adjunct therapy to (Da, Zhu, Wang, & Sun, 2015). An in vivo study in nude mice showed that the combination of curcumin (10 mg/kg/day intraperitoneally) and 5-FU (33 mg/kg/ twice weekly intraperitoneally) and oxaliplatin (10 mg/kg intraperitoneally once) has powerful growth inhibition of BGC-823 xenograft tumors.…”
Section: In Vitro Chemosensitizing Activity Of Curcumin Against Gasmentioning
confidence: 99%